1991
DOI: 10.1111/j.1468-2257.1991.tb00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Metropolitan Growth and Decline in the United States: an Empirical Analysis

Abstract: "Urban growth rates are documented for the largest United States Metropolitan Statistical Areas for the periods 1965-70 and 1975-80. The spatial pattern associated with these growth rates tends to reinforce the sunbelt-frostbelt dichotomy, as the majority of cities with positive migration rates for both time periods are located outside of the heavily industrialized Northeast and Midwest regions of the country. Two and three-group discriminant analyses indicate that manufacturing activity, local tax rates, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…This zone became a magnet for people from outside the metropolitan area (Cadwaller, 1991;Morrill, 1992). The urbanization process of the innermost zone helped to expand the urban areas and increase the diversity of land use on the fringes of the metropolitan areas.…”
Section: Population Growth and Spatial Extension Trendsmentioning
confidence: 98%
“…This zone became a magnet for people from outside the metropolitan area (Cadwaller, 1991;Morrill, 1992). The urbanization process of the innermost zone helped to expand the urban areas and increase the diversity of land use on the fringes of the metropolitan areas.…”
Section: Population Growth and Spatial Extension Trendsmentioning
confidence: 98%
“…By analysing the average maximum temperatures in January and July for U.S. counties from the 1880s to the 1990s, that author found that lower maximum and higher minimum temperatures helped explain patterns of population growth. Cadwallader () discovered for U.S. cities between 1975 and 1980 that the level of climatic attractiveness was greater in growing cities. For Europe, Cheshire and Magrini (), considering the former EU‐12 countries, did not find any evidence that weather influenced mobility between countries but did find it relevant for mobility within countries, whereby “warm days” measured by an upper value of heat, dryness, or sunshine favour higher city population growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Somewhat to the authors' surprise, the bulk of the population decline (78.8%) occurred in the relatively small number of losing metro counties which tend to be concentrated in the northeastern quarter of the country. Much has been written about the problems of these cities, in particular the inner-city deterioration and the outward relocation of people to nearby suburbs and more distant exurban areas often beyond formal metro boundaries (Cadwallader 1991, Morrill 1992, Sternlieb and Hughes 1975. As a whole, population loss in these metro counties has been entirely the result of high net outmigration (surplus of outmigrants over inmigrants), because the natural population growth rate is well above the national average.…”
Section: Overall Characteristics Of Counties Losing Populationmentioning
confidence: 99%